ABUNDANCE AND COMPOSITION OF ROTIFERS IN A POND NEAR BALLOKI HEADWORKS - A. Q. K. Sulehria; R. Mushtaq; M. Ejaz (Journal of Animal and Plant Sciences, 2012)
In present study, rotifer species and their seasonal variation were determined along with physical and chemical parameters of water from December 2009 to June 2010. Mostly highest and lowest values of physical and chemical parameters were observed in summer and winter seasons. Analysis of variance (P=0.926) showed that there was significant difference in the Physical-chemical characteristics of water in different seasons. 12 species belonging to 7 genera were identified in this area. Only three species were present in all seasons which included Brachionus quadridentatus, Polyarthra vulgaris and Trichocera similis. Highest mean values (6.75±2.51) of rotifers were observed in spring season. Lowest mean values rotifers (4.08±1.86) were found in autumn season. In summer and winter season the mean values for rotifer were (5.25±2.16) and (5.67±2.55) found.
Keywords: Planktonic rotifers; Physical-chemical parameters; Brachionus; Polyarthra; Trichocera.